FRI0085 TAPERING OF BIOLOGICAL ANTIRHEUMATIC DRUGS IN RHEUMATOID ARTHRITIS PATIENTSIS ACHIEVABLE AND COST EFFECTIVE IN DAILY CLINICAL PRACTICE: DATA FROM THE BRUSSELS UCL RA COHORT. (June 2019) - Dierckx, Stephanie; Lauwerys, Bernard; Sokolova, Tatiana; Bellefon, Laurent Meric de; Stoenoiu, Maria; Nzeusseu, Adrien; Houssiau, Frederic; Avramovska, Aleksandra; Durez, Patrick
Abstract : Background: Several studies have demonstrated that Rheumatoid Arthritis (RA) patients achieving low disease activity or remission are able to taper biological disease-modifying antirheumatic drugs (bDMARDs). Objectives: The aim of this study is to evaluate the proportion of patients in whom the bDMARD can be tapered in daily practice and to analyse the characteristics of these patients e. Another objective is to determine which bDMARDs are more adapted to dose reduction and the cost saving. Methods: Inclusion criteria were RA patients from our Brussels UCL cohort treated with a bDMARD for at least one year. A dose reduction was proposed by the senior physician when sustained low disease activity or remission was achieved. Patient characteristics and baseline features before the introduction of the current bDMARD were collected as well as flares if happened. We also calculated, for each bDMARD, the proportion of patients who received a decreased dose and the annual cost. Results: Data from 332 eligible RA patients were collected, 140 patients (42, 1%) had a tapered regimen and 192 received a full dose of bDMARD. In the decreased dose group, age at diagnosis (43.1 vs 38.7 years, p=0.004), HAQ (1.3 vs 1.5, p=0.048), RF (83.3 vs 72.9%, p=0.026) and disease duration at the bDMARDs introduction (9.7 vs 12.1 years, p=0.034) were statistically different. As expected, the current DAS28-CRP was lower (2.26 vs 2.64, p=0.001) in the decreased dose group and interestingly, more patients receiving a decreased dose were treated with a combination of methotrexate when the bDMARD was introduced (86.7% vs 73.8%, p=0.005). No difference between groups was observed for gender, ACPA, erosion, number of previous bDMARDs, time to first conventional synthetic DMARD and biological DMARD, baseline DAS28-CRP and use of glucocorticoids. In our cohort, anti-TNF agents were the most commonly prescribed medications (anti-TNF 68%, tocilizumab 15%, rituximab 10%, abatacept 7%). Only 15 patients experienced a flare during the follow-up. Adalimumab, etanercept and rituximab were the most frequent decreased bDMARD and were associated with the most important reduction of annual cost. ABA : abatacept, ADA : adalimumab, CZP : certolizumab, ETN : étanercept, GOL : golimumab, IFX : infliximab, RTX : rituximab, TOC : tocilizumab Conclusion: In daily practice, tapering of bDMARDs in RA patients with low disease activity or remission is an achievable goal in a large proportion of patients, thereby reducing annual drug cost. The combination with methotrexate could be a positive predictive factor for the success of bDMARD tapering but further prospective research in daily practice are needed to confirm this result. Disclosure of Interests: Stephanie Dierckx: None declared, Bernard Lauwerys: None declared, Tatiana Sokolova: None declared, Laurent Meric de Bellefon: None declared, Maria Stoenoiu Grant/research support from: Abbvie, Roche, Wyeth, Adrien Nzeusseu: None declared, Frederic Houssiau: None declared, Aleksandra Avramovska: None declared, Patrick Durez Speakers bureau: Bristol-Myers Squibb, Eli Lilly, Sanofi, Celltrion